I dont get anything about negative answers they all just make my brain hurt.

-3 is the additive inverse of 3

That is -3+3=0

If we borrow $3, then we are liable for $3, we say it is -3

When we get an income of $3, we retire that loan .Therefore -3+3=0

If we borrow $3 and borrow $4 from someone else, our total borrowing is 7 i.e is -7

-3+(-4) =-3-4=-7

If we borrow $3 and get loan $4 given to someone is returned,

-3-(-4)=-3+4=1

These are the simple rules

(-3)+(-4) =-3-4=-7

(-3)-(-4) =-3+4=1

(-3)*4=-12

(-3)*(-4)=12

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up